2020
DOI: 10.1038/s41398-020-00948-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between DNA methylation levels in brain tissue and late-life depression in community-based participants

Abstract: Objective: Major depressive disorder (MDD) arises from a combination of genetic and environmental risk factors and DNA methylation is one of the molecular mechanisms through which these factors can manifest. However, little is known about the epigenetic signature of MDD in brain tissue. This study aimed to investigate associations between brain tissue-based DNA methylation and late-life MDD. Methods: We performed a brain epigenome-wide association study (EWAS) of late-life MDD in 608 participants from the Reli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Thus, abnormalities in the Slit/Robo pathway are observed in these neuropsychiatric disorders. There is increasing evidence that suggest Slit2 is associated with some neuropsychiatric disorders, including MDD (Huls et al, 2020), AD (Li et al, 2015), Parkinson's disease (PD) (Lin and Isacson, 2006), TLE (Fang et al, 2010), and ASD (Perez et al, 2016;Gorker et al, 2018). Depression and anxiety are common psychiatric disorders, and their pathogenesis is not well-understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, abnormalities in the Slit/Robo pathway are observed in these neuropsychiatric disorders. There is increasing evidence that suggest Slit2 is associated with some neuropsychiatric disorders, including MDD (Huls et al, 2020), AD (Li et al, 2015), Parkinson's disease (PD) (Lin and Isacson, 2006), TLE (Fang et al, 2010), and ASD (Perez et al, 2016;Gorker et al, 2018). Depression and anxiety are common psychiatric disorders, and their pathogenesis is not well-understood.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studying the molecular mechanisms of depression/anxiety is crucial. An epigenome-wide association study (EWAS) of MDD patients found that altered methylation in the Slit2 locus is associated with late-life depression (Huls et al, 2020). However, there is little clinical evidence that Slit2 is associated with FIGURE 5 | The messenger RNA (mRNA) expression levels of 5-HT1AR, BDNF, GR, TNF-α, IL-6, and IL-1β in the hippocampus of mice.…”
Section: Discussionmentioning
confidence: 99%
“…[ 164 ] In an EWAS last year based on the association between DNA methylation in brain tissue and depression, reliable CpG loci were identified in the YOD1 exon, PFKFB2 intron, UGT8 , FNDC3B , and SLIT2 regions. [ 165 ] Of these, YOD1 has been shown to be associated with mechanisms of multiple neurodegenerative diseases and UGT8 is a known biomarker gene for depressed mood. [ 166 , 167 ] These CpG loci hold promise as epigenetic markers of depression and for application in clinical drug development trials.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, most DNA methylation studies have used candidate gene approaches and have been predominantly focused on gene promoter regions [ 15 , 16 , 17 ]. Accompanied by the rise of DNA methylation chip arrays and whole-genome bisulfite sequencing technology, several attempts have been made to decipher the relationship between DNA methylation and depression [ 18 , 19 ]. Although many genome-wide studies have indicated that DNA methylation is associated with depression, both positive and negative associations have been reported, and conflicting results are often observed [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%